Design of control signal for electrical drive system for technology demonstrator - Mohd Hasnul Mubakir, Osman (2013)
Drive System for Omni-directional 4 wheel mobile platform consists of combination between electrical mechanism and mechanical mechanism. The most important part for this Mobile Platform is to drive the DC Motor. The control system development from digital signal provided by transmitter and receiver (Remote Control) to control the Motor Speed is the main problem for this study. This study also required the research on conversion of digital signal to digital signal (DC-to-DC) by using Programmable Integrated Circuit (ATMega 328P). This study is very important not only to drive the DC motor but it also help to read information from any sensor signal (analog and digital) and providing a readable data display. The research on Digital Signal from receiver also has been made during this study. The advance Remote Control such as FUTABA has its own PWM signal with its own fix frequency and duty cycle. By using 555 timer, Receiver PWM Wave Generator has been made. This device is able to change its frequency and duty cycle freely. This generator helps this study to build up a receiver signal as same as other Advance Remote Control Receiver signal.